Navigating Towards an Airworthy Protection Regime for New Zealand's Airline Passengers - Macey, James (Victoria University of Wellington Law Review, 2025)
Delays and cancellations are a frequent occurrence in air travel, but passenger protections in New Zealand lag behind those in other jurisdictions such as the European Union and Canada. Concerns around airlines' treatment of passengers were brought to the fore during the COVID-19 pandemic, but protections were not strengthened in the replacement of the Civil Aviation Act 1990 with the Civil Aviation Act 2023. The new Act provides insufficient protection to passengers, and New Zealand's other consumer law is also inadequate and difficult to apply to an airline context. Neither set of law has a dispute resolution scheme that is fit for purpose. Public enforcement of relevant laws by regulators is limited to breaches of the Fair Trading Act 1986, largely for misleading or deceptive trading practices, and not for breaches of specific obligations to passengers. This article examines the deficiencies in New Zealand's airline passenger protection law and compares that law with the corresponding law in Australia, the European Union and Canada. It advocates for the making of regulations that provide for fixed amounts of compensation when a flight is delayed for controllable reasons, rather than laws which require a passenger to prove damages. That is consistent with the European and Canadian approaches. It also advocates for refunds to be made available to passengers where flights are cancelled or significantly delayed. To ensure that new regulations would be effective, this article also advocates for an adjudicative dispute resolution scheme, funded by airlines according to their market share and the number of complaints received, with capacity for public enforcement (monetary fines) by the Commerce Commission.